The Role of the Ministry of Law in Harmonizing National Legislation and International Legal Standards - Haning, Semuel; Putri, Vegitya Ramadhani; Indriasari, Evy (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2026)
This study examines the role of the Ministry of Law in harmonizing national legislation with international legal standards, focusing on the challenges and mechanisms involved in aligning domestic laws with global norms. With increasing globalization, countries are increasingly required to adjust their legal systems to comply with international treaties and agreements. This research aims to explore how the Ministry of Law facilitates this process, addressing the political, legal, and institutional challenges that arise in the harmonization process. A qualitative literature review was conducted, analyzing relevant academic sources, governmental reports, and case studies from various countries. The findings reveal that while the Ministry of Law plays a pivotal role in implementing international legal standards, its success is often contingent on institutional capacity, political will, and the ability to balance national interests with international obligations. The study concludes that a strategic, well-supported Ministry of Law is essential for effective legal harmonization. Strengthening the Ministry’s capacity and fostering intergovernmental cooperation are key to overcoming resistance and ensuring compliance with international legal standards, ultimately enhancing global legal cooperation and governance.